2020
DOI: 10.3390/nu12082276
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Seafood Intake and Fecundability: Analysis from Two Prospective Studies

Abstract: Background: Seafood is an important source of omega-3 fatty acids, which have been associated with improved oocyte quality and embryo morphology in some studies. However, seafood is also a source of persistent organic pollutants and heavy metals, which may adversely affect fecundity. Previous studies of seafood intake and fecundity have generated inconsistent results. Methods: In two prospective cohort studies of 7836 female pregnancy planners from Denmark (Snart Foraeldre, n = 2709) and North America (PRESTO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Although there are a relatively large number of reports about dietary habits including consumption of seafood and fish, there are no consistent reports about whether seafood consumption positively affects fertility (5,(37)(38)(39). The reason for these inconsistent results may be that seafood contains both fertilityenhancing and -damaging substances.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a relatively large number of reports about dietary habits including consumption of seafood and fish, there are no consistent reports about whether seafood consumption positively affects fertility (5,(37)(38)(39). The reason for these inconsistent results may be that seafood contains both fertilityenhancing and -damaging substances.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study methods have been described elsewhere (Mikkelsen et al, 2016;Wise et al, 2020). In brief, enrollment is ongoing and began in June 2011 for SF and June 2013 for PRESTO, which was modeled after SF.…”
Section: Methodsmentioning
confidence: 99%
“…Locally, in Singapore, the time required to achieve a clinical pregnancy exceeds a year for about 15% of couples (5). Existing studies have reported modest associations between intakes of specific foods/ beverages (such as dairy (6), seafood (7), diet soda and fruit juice (8)] or nutrients [such as total fat, specific types of fats and fatty acids (9), glycemic load, added sugar (10) and iron (11)]) and fecundability. However, studies examining overall diets, which takes into account the synergistic effects of individual dietary components on diet-fecundability associations, are limited.…”
Section: Introductionmentioning
confidence: 99%